Vascular Flora of Bala-Fort Forest in Alwar, Rajasthan - Yadav, R. K.; Yadav, Atar S. (Indian Forester, 2006)
The Bala-fort forest is surrounded by a high wall (parkota), it is, therefore, considered as the most protected forest in this region since the establishment of Alwar State in 1775. Although Anogeissus pendula is the most dominant species, 22 tree, 17 shrub and 151 herbaceous plant species also grow in this forest. Some of the important medicinal plants such as Acacia catechu, Commiphora wightii, Kickxia ramosissima and Sterculia urens prefer to grow in the undisturbed environment of this forest. The growth of Desmodium repandum and Melhania futteyporensis is also restricted to this natural habitat.